PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SINONIM DAN ANTONIM DI KELAS V UPTD SD NEGERI BALFAI - Elisabet Letek, Viligonsia; Robot, Marselus; Bol Nifu Benu, Adam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled "The Application of the Make a Match Cooperative Learning Model in Improving Student Learning Outcomes on Synonyms and Antonyms in Class V of UPTD SD Negeri Balfai". This research is motivated by the low student learning outcomes on synonyms and antonyms in class V of UPTD SD Negeri Balfai, with the aim of improving student learning outcomes through the application of the Make a Match cooperative learning model. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects are 24 students. Data collection techniques used include observation, tests, and documentation. Data are analyzed using quantitative and qualitative descriptive analysis techniques. The results of the study indicate that the application of the Make a Match cooperative learning model can improve student learning outcomes on synonyms and antonyms. At the pre-cycle stage, the average value of student learning outcomes was 47.91 with a learning completion percentage of 16.67%. After the actions in cycle I, the average score increased to 61.67, with a learning completion percentage of 37.5%. In cycle II, the average score increased again to 80.41, with a learning completion percentage of 91.67%. Based on the research results, it can be concluded that the implementation of the Make a Match cooperative learning model is effective in improving student learning outcomes, motivation, and cooperation, as well as creating active and enjoyable. Keywords: Make a Match, Learning Outcomes, Synonyms and Antonyms